Menyingkap Fenomena Alam Semesta Bertasbih dan Bersujud (Studi Korelasi antara Ayat-ayat Kauniyah dengan Ayat-ayat Qauliyah) - Solihin, Misbakhul khaer; Santi, Mei (Program Studi Ilmu Al-Quran dan Tafsir, 2023)
In the beginning, many ordinary people assumed that lifeless objects (al-Jama>da>t) are inanimate objects that are static, inactive, and not developing. But the presence of science proves the untruth of this assumption and the Qur’an turns out to be 1400 years ago has first revealed the facts. The Qur’an although not a book of science, explicitly guides and instructs humans to read, observe, and conduct a series of research and trials on the symptoms of the universe’s phenomena. phenomena of the universe that are so powerful. This paper aims to uncover part of the macrocosm, which is the verses of Kauniyah, which are clearly stated by the verses of Qauniyah. Clearly stated by the Qauliyah verses of glorifying and prostrating, then the two types of verses are harmonized, so that it is found that the content of the Qur’an does not contradict modern science which continues to experience does not contradict modern science which continues to develop. This research is a literature type, with qualitative methods and using a descriptive-narrative approach. As for the results of the study, by referring to the opinions of the commentators regarding the universe of dhikr, praise, and prostration, it shows that there is a very close relationship between the verses of Kauniyah as sunnatullah with the verses of Qauliyah, where both come from Allah SWT. Between Qauliyah verses and Kauniyah verses both reinforce each other, Qauliyah verses reinforce the truth of Kauniyah verses, and vice verses, Kauniyah verses reinforce the truth of Qauliyah verses. Thus the microcosm (atoms) and macrocosm rotate/circulate or surround the center of the solar system is a form of tasbih and prostration (submission) to the Creator in order to maintain its balance from destruction.